IFNγ modulates human immunoglobulin receptor expression in lipoaspirate-derived mesenchymal stem cells (Faculty of Medicine Universitas Indonesia, 2014)
Background: Mesenchymal stem cell (MSC) has been reported to have immunomodulator capacity against autoimmune diseases and to prevent allogenic tissue rejection. Many studies revealed that MSC’s inhibit T cell proliferation and induce immunosuppressive condition through the production of prostaglandins, and interleukin-10. In addition, MSC was reported to reduce circulating autoantibody in autoimmune patients following MSC transfusion. So far, there has been no report stating the presence of Fc receptors (receptors for immunoglobulin) on MSCs. The aim of this study was to reveal the expression of FcγRs in lipoaspirate-derived MSCs by measuring transcription of FcγR mRNA and whether the expression can be modulated. Methods: Lipoaspirate-derived MSCs were cultured in suitable medium and confirmed to be MSCs according to the criteria published by International Society for Cellular Therapy. Total mRNA of MSCs was isolated, and detection of human FcγRI, FcγRIIA and FcγRIIB mRNA was performed. Further, modulation of the expression was tested using heat aggregated gamma globulin (HAGG) and interferon (IFN)γ. Results: FcγRs mRNA was detected in the first passage of MSCs. However, the expression was no longer present after more than 4 passages. Further, increased level of FcγRI and FcγRIIA mRNA expression was detected with the addition of IFNγ in the culture. This preliminary finding opens a new insight for the understanding of interaction between MSCs and immunoglobulin G through FcγRs. Conclusion: Lipoaspirate-derived MSCs express FcγRs, and the expression is modulated by IFNγ.